Una máquina teatral: Forma e identidad en el teatro de Migdalia Cruz - Santana, Analola (Latin American Theatre Review, 2010)
Migdalia Cruz’s work stands out for its aesthetics, and because of the themes and characters that she so carefully develops through a focus on the scatological elements that compose the body as a form of grotesque beauty. This essay studies two particular plays,Miriam’s Flowers (1992) and Fur (2000), focusing on the aesthetics that compose her works in relation to two specific dominant issues: love and sexuality. It is through these themes that hercharacters develop a sense of agency and it is possible to identify a concern towards identity construction that forms part of Migdalia Cruz’s theatrical corpus. (AS, Article in Spanish)